Sleep quality and anxiety levels among university students: 10.15343/0104-7809.202246247254 - Nogueira Silva, Dalaine (2022)
The present article seeks to describe the quality of sleep and excessive daytime sleepiness of university students and to verify the levels of trait anxiety (A-Trait) and state anxiety (A-State) presented by them. A sample, composed of undergraduate students from daytime courses, responded to an online form, containing the following questionnaires: Sociodemographic; Epworth Sleepiness Scale; Pittsburgh Sleep Quality Index; and State-Trait Anxiety Inventory. A descriptive analysis of the data was then performed. The mean age of the 305 participants was 22 ± 2.99 years, 51.37% were female, 98.03% were non-smokers, 52.8% consumed alcohol, and 54.1% practiced physical activity. The majority demonstrated an absence of excessive daytime sleepiness (62.3%), poor sleep quality (72.4%), and moderate levels of A-Trait (56.4%) and A-State (47.2%). The main findings of this study reveal that the volunteers have poor sleep quality with a moderate level of state-trait anxiety. The results also indicate that the profile of the students who answered the questionnaire was composed of young adults who did not have an employment relationship and were single. There was poor sleep quality among university students. In addition, state trait anxiety scores were at moderate levels.